2010
DOI: 10.1080/02601370903471304
|View full text |Cite
|
Sign up to set email alerts
|

The politics of ESOL (English for speakers of other languages): implications for citizenship and social justice

Abstract: , UK). His main field of research is the comparative (historical and sociological) study of education and training systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…The course seemed to have contributed to a changed understanding of the UK. All the students said that they had become more aware of the country's diversity concerning ethnic cultures, religions and nationalities, something which they regarded as positive (Han et al, 2010). Further, the authors found that civic participation was not the adult students' first purpose with the course, but rather they had practical considerations, such as improving their English skills and obtaining employment.…”
Section: Migrants' Experiences Of Civic Education Coursesmentioning
confidence: 87%
See 2 more Smart Citations
“…The course seemed to have contributed to a changed understanding of the UK. All the students said that they had become more aware of the country's diversity concerning ethnic cultures, religions and nationalities, something which they regarded as positive (Han et al, 2010). Further, the authors found that civic participation was not the adult students' first purpose with the course, but rather they had practical considerations, such as improving their English skills and obtaining employment.…”
Section: Migrants' Experiences Of Civic Education Coursesmentioning
confidence: 87%
“…Thus, their motives were more personal than civic. Nevertheless, Han et al (2010) conclude that their findings indicate that the language and citizenship course gives migrants confidence, and helps them find their way in their new country, thus helping them to become established socially and financially too. It is also found that the course could facilitate basic kinds of civic participation, such as voluntary work at one's child's school (Ibid.).…”
Section: Migrants' Experiences Of Civic Education Coursesmentioning
confidence: 96%
See 1 more Smart Citation
“…The link was also made explicit in the Community and Cohesion Report into the riots (Cantle, 2001), although this correlation was widely disputed (e.g. Han, Starkey & Green, 2010).…”
Section: Language and Societymentioning
confidence: 99%
“…This privileging of skills and socio-economic capital is compounded by the nature of examination itself, as it requires a certain level of educational merit, literacy and communication skills. This is especially relevant to not only the multiple-choice test with its emphasis on self-learning but also the ESOL course which relies on institutional education (Han, Starkey, and Green 2010). The practice of actually sitting an examination, like learning in a classroom, is something which is normalised within certain cultural and class frameworks (Löwenheim and Gazit 2009).…”
Section: Responsibility: An Economic Sacrificementioning
confidence: 99%